Competitiveness and Determinant of Indonesian Processed Cocoa Demand in the AANZFTA Framework - Yemima, Renery; Novianti, Tanti (Jurnal Ilmu Ekonomi Terapan, 2020)
Indonesia is one of the biggest producer of cacao beans in the world. Export tariff policy on cacao bean and countries trade agreement was expected can increase the processed of cacao export. This research aims to analyze the competitiveness and the determinants of which affect the processed cacao export in AANZFTA Region countries. Based on RCA anaylsis, the processed cacao has been comparative advantage, and its EPD analysis show that Indonesia's processed cacao mostly in falling star and retreat condition. The result of regression analysis panel data showed that the export of cacao paste was affected significantly by exchange rate, Indonesia's export competitiveness, and free trade area policy. Cacao butter was affected significantly by exchange rate, Indonesia's export competitiveness, and free trade area policy. Cacao powder was affected significantly by gross domestic product total, exchange rate, Indonesia's export competitiveness, and free trade area policy.